Effect of nickel on nutrient removal by selected indigenous protozoan species in wastewater systems - Kamika, Ilunga (Saudi J Biol Sci, 2014)
Nutrient and heavy metal pollutions are major concern worldwide. This study aimed at comparing the effect of Ni(2+) on nutrient removal efficiency of four indigenous wastewater protozoan species (Aspidisca sp., Paramecium sp., Peranema sp., Trachelophyllum sp.). Specific physicochemical parameters and microbial growth/die-off were measured using standard methods. The results revealed that protozoan species were able to simultaneously remove phosphate, nitrate and Ni(2+) at concentrations ranging between 66.4–99.36%, 56.19–99.88% and 45.98–85.69%, respectively. Peranema sp. appeared to be the isolates with the highest removal of nutrients (Phosphate-99.36% and Nitrate-99.88%) while Paramecium sp. showed higher removal of Ni(2+) at 85.69% and low removal of nutrients. Aspidisca sp. was the most sensitive isolate to Ni(2+) but with significant nutrient removal (Phosphate-66.4% and Nitrate-56.19%) at 10 mg-N(2+)/L followed by an inhibition of nutrient removal at Ni(2+) concentration greater than 10 mg/L. Significant correlation between the growth rate and nutrient removal (r = 0.806/0.799, p < 0.05 for phosphate and nitrate, respectively) was noted. Except for Peranema sp. which revealed better nutrient removal ability at 10 mg-Ni(2+)/L, an increase in Ni(2+) concentration had a significant effect on nutrient removal efficiency of these indigenous protozoan species. This study suggests that although Ni(2+) appeared to be toxic to microbial isolates, its effect at a low concentration (10 mg-Ni(2+)/L) towards these isolates can be used to enhance the wastewater treatment process for the removal of nutrients. Peranema sp., which was able to remove both Ni(2+) and nutrients from wastewater mixed-liquor, can also be used for bioremediation of wastewater systems.